2020
DOI: 10.1016/j.cegh.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The socioeconomic correlates of substance use among male adults in Northeast India

Abstract: Background: Substance use-defined by the consumption of alcohol, smoking, and smokeless tobacco-has been identified as a serious health hazard in India. Understanding the socioeconomic correlates of substance use in Northeast India (NEI) will provide crucial input for public health policies in this region. Objectives: To examine the socioeconomic correlates of substance consumption among male adults of NEI. Data and methods: We analyzed nationally representative data from the National Family Health Survey (NFH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…The present study reconfirms a similar pattern of disparity by castes and household WQ (Subramanian et al 2006;Po and Subramanian 2011;Saikia and Ram 2010). The mortality disadvantage among adults from deprived castes may be linked to higher prevalence of substance abuse (Saikia and Debbarma 2019), or economic and social discrimination (Banerjee and Knight 1985;Sil &Dhillon, 2017, Ira, Sen andYun, 2012). Previous studies also discussed the advantage of survival of the Muslim population in India.…”
Section: Discussionsupporting
confidence: 83%
“…The present study reconfirms a similar pattern of disparity by castes and household WQ (Subramanian et al 2006;Po and Subramanian 2011;Saikia and Ram 2010). The mortality disadvantage among adults from deprived castes may be linked to higher prevalence of substance abuse (Saikia and Debbarma 2019), or economic and social discrimination (Banerjee and Knight 1985;Sil &Dhillon, 2017, Ira, Sen andYun, 2012). Previous studies also discussed the advantage of survival of the Muslim population in India.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, the use of both smokeless and smoked tobacco, alcohol and cannabis (a psychoactive drug) is widely prevalent among the adolescents residing in the Indian slums [11]. Existing studies had linked the substance usage among adolescents with age [12], education [13], poverty [14], migration and occupation exploitation [15], creating cool image among peers [16], working status [17], drug culture [18], socioeconomic correlates [19]. Moreover, substance use among the family members has also emerged to be an important predictor of substance use among adolescents in both developed and developing countries [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Other than a geospatial study of alcohol use based on 1998's Special Fertility and Mortality Survey (16), very little information is available on the statistically significant hot spot clusters of alcohol consumption at the district level in India. Even though earlier studies have reported the socioeconomic determinants of co-use of alcohol and tobacco, and substance use among North-East (NE) men (17,18), the sociodemographic risk factors of alcohol use in Indian men (or women) have not been studied. The data from NFHS-4 were used for Geographic Information System (GIS) and spatial statistics to map the major alcohol hot spots in India.…”
Section: Introductionmentioning
confidence: 99%